Progress in Cryptology -- INDOCRYPT 2017 : 18th International Conference on Cryptology in India, Chennai, India, December 10-13, 2017, Proceedings /: 18th International Conference on Cryptology in India, Chennai, India, December 10-13, 2017, Proceedings. (2017) - Unknown
No abstract available